The “field work”, as a source for the formation of an integral professional supportive of Public Health (Revista Venezolana de Salud Pública, 2019)
The importance of “Field Work” as a relevant for activity in the comprehensive training of integral health professionals with a vision of public health support it’s briefly described. The excellent results obtained in 1990 with the XX promotion of the Shool of Biotechnology are presented, through the experience developed by the Parasitology Departament of the Carabobo University in Valencia, Carabobo State, Venezuela
Keywords: field work; public health; education; Parasitology